Answers

2014-08-21T15:59:01+05:30
(a)
Formula used: a^{3} -  b^{3} = (a - b) (a^{2} + ab +  b^{2})

250 x^{3} - 432 y^{3} \\ 
= 2 [125 x^{3} - 216 y^{3}] \\ 
= 2 [5^{3} x^{3} - 6^{3} y^{3}] \\ 
= 2 [(5x)^{3} - (6y)^{3}]

Now use the formula
=2 [(5x - 6y) (25 x^{2} + 30xy + 36 y^{2})] \\ 
=2(5x - 6y) (25 x^{2} + 30xy + 36 y^{2})

(b)
x^{2} + 3 \sqrt{3}x - 30 \\ = x^{2} - 2 \sqrt{3}x + 5\sqrt{3}x - 30\\ = x(x - 2 \sqrt{3}) + 5\sqrt{3}(x - 2 \sqrt{3}) \\ = (x - 2 \sqrt{3})(x + 5 \sqrt{3})
1 5 1
Umm the b) one is too complicated and I'm studying in class 9 so I need the easy basic method
complicated ??
No it's ok